Association between Dietary Magnesium Intake and Lipid Profile Parameters in Obese Women (Research, Society and Development, 2020)
Introduction: Obesity is associated with the development of other chronic diseases, such as dyslipidemia, characterized by increased plasma concentrations of triglycerides, total cholesterol (TC) and LDL-c and reduction of HDL-c. In order to identify mechanisms involved in these disorders, magnesium has been studied for regulating important enzymes in lipid metabolism. Objective: To evaluate the relationship between dietary magnesium content and lipid profile in obese women. Methodology: Cross-sectional and analytical study with women divided into two groups: case (obese, n = 25) and control (eutrophic, n = 42). Magnesium intake was analyzed by a three-day food record using the Nutwin program. Serum lipid concentrations were determined according to the colorimetric enzymatic method in an automatic biochemical analyzer. Results: Macronutrient intake values were within the recommended ranges in both groups. Magnesium intake was below the recommendations, with no statistical difference between the studied groups (p> 0.05). Serum TC and LDL-c concentrations were higher and HDL-c lower in obese women compared to eutrophic women (p